İlaç Hedefli Karbonil Bileşiklerinin Sentezi - Kahraman, Selime (Fen Bilimleri Enstitüsü, 2013)
Anaç ve ekibinin yaptıkları çalışmalarda, α, β-doymamış karbonil bileşikleri ile diazo bileşiklerinin katalitik ortamdaki reaksiyonlarını incelemiştir. Bu reaksiyonlarda sıklıkla dihidrofuran türevlerine rastlanmıştır. Bu ürün oluşumu [1,5]- elektrosiklik halka kapanması reaksiyonu üzerinden gerçekleşmektedir. Bu reaksiyonların gerçekleşebilmesi için α, β-doymamış karbonil bileşiklerinin, β-pozisyonlarında, uygun geometriye sahip bir hidrojen taşımaları ve ayrıca bu bileşiklerin, s-cis konformasyonunda olmaları gerektiği sonucuna varılmıştır. Konjugasyonun daha da uzatıldığı çıkış bileşiklerinin analog reaksiyonlarında [1,5]- elektrosiklik halka kapanması reaksiyonunun yanısıra [1,7]- elektrosiklik halka kapanması reaksiyonunun da oluştuğu gözlenmiştir. Ekibin önceki çalışmalarına paralel olarak bu tez çalışmasında, α, β,γ,δ-doymamış diketon, diester ve keto-esterler bileşiklerinin bakır(II) asetilasetonat veya Rh(II) asetat katalizörleri varlığında, çeşitli diazo bileşikleriyle reaksiyonları incelenmiştir. Bu amaç doğrultusunda öncelikle, sadece karbonil gruplarında farklılık gösteren ve δ-konumunda furan grubu içeren üç adet farklı α, β,γ,δ-doymamıs dikarbonil bilesiği sentezlenmistir. Bu bileşikler: (E)-dimetil 2-(3-(furan-2-il)alliliden)malonat, (E)-3-(3-(furan-2-il)alliliden)pentan-2,4-dion ve (2E/Z,4E)-etil 2-asetil-5-(furan-2-il)penta-2,4-dienoat’dır. Daha sonra, sentezlenen bu bileşiklerin çeşitli diazo bileşikleri ile katalitik ortamdaki reaksiyonları incelenmiştir. İlk olarak: sentezlenmiş analog yapılardaki üç adet konjuge karbonil bileşiğinin ayrı ayrı dimetil diazomalonat (akseptör-akseptör özellikli karbenoid verir) ile bakır(II) asetilasetonat katalizörlüğünde reaksiyonları gerçekleştirilmiştir. (E)-Dimetil 2-(3-(furan-2-il)alliliden)malonat ile gerçekleştirilen reaksiyonda -ekibin daha önceki çalışmalarından farklı olarak- furan üzerinde oluşan siklopropanın halka açılma ürünü olan (3E/Z,6E)-tetrametil 5-oksonon-1,3,6,8-tetraen-1,1,9,9-tetrakarboksilat bileşiği elde edilmiştir. Reaksiyon Rh(II) asetat katalizörü ile tekrarlandığında yine aynı ürünün oluştuğu görülmüştür. (E)-3-(3-(furan-2-il)alliliden)pentan-2,4-dion bileşiğinin dimetil diazomalonat ile bakır(II) asetilasetonat katalizörlüğünde reaksiyonu incelendiğinde ise karbonil ilid üzerinden [1,5]-elektrosiklik halka kapanma ürünü ((E)-dimetil 4-asetil-3-(2-(furan-2-il)vinil)-5-metilfuran-2,2(3H)-dikarboksilat) tek ürün olarak elde edilmiştir. Dimetil diazomalonatın (2E/Z,4E)-etil 2-asetil-5-(furan-2-il)penta-2,4-dienoat bileşiği ile analog reaksiyonunda karbonil ilid üzerinden [1,7]-elektrosiklik halka kapanma ürünü olan 6-etil 2,2-dimetil 3-(furan-2-il)-7-metiloksepin-2,2,6(3H)-trikarboksilatın tek ürün olduğu görülmüştür. (E)-Dimetil 2-(3-(furan-2-il)alliliden)malonat bileşiğinin dimetil diazomalonat ile [1,5]/[1,7]-elektrosiklik halka kapanma reaksiyonlarını vermeyip sadece poli-fonksiyonlu polien vermesi dikkat çekicidir. Bu nedenle araştırmanın yönü bu diesterli konjuge çıkış bileşiğinin dimetil diazomalonattan (akseptör-akseptör özellikli karbeboid verir) daha farklı karakterlerdeki diazo bileşikleriyle olan reaksiyonlarına yönlendirilmiştir. Bu amaçla etil diazoasetat (akseptör), 1-diazo-1-fenilpropan-2-on (donör-akseptör), (E)-metil 2-diazo-4-fenilbut-3-enoat (donör-akseptör) ile reaksiyonlar gerçekleştirilmiştir. Etil diazoasetat ile Rh(II) asetat katalizörleri varlığında gerçekleştirilen reaksiyonda da sadece furan üzerinde oluşan siklopropanın halka açılmasıyla oluşan (3E,6E,8E)-9-etil 1,1-dimetil 5-oksonon-1,3,6,8-tetraen-1,1,9-trikarboksilat ele geçmektedir. Aynı reaksiyon bakır(II) asetilasetonat katalizörlüğünde gerçekleştirildiğinde de aynı ürünün oluştuğu görülmüştür. Donör-akseptör özellikli 1-diazo-1-fenilpropan-2-on ile Rh(II) asetat katalizörleri varlığında gerçekleştirilen reaksiyonda karbonil ilidin [1,5]-elektrosiklik halka kapanma ürünü olan (E)-metil 5-asetil-4-(2-(furan-2-il)vinil)-2-metoksi-5-fenil-4,5-dihidrofuran-3-karboksilat bileşiği elde edilmiştir. Diğer bir donör-akseptör özellikli (E)-metil 2-diazo-4-fenilbut-3-enoat bileşiği ile Rh(II) asetat katalizörlüğündeki reaksiyonda ise çıkış bileşiği ile reaksiyon gözlenmemiştir. Bunun yerine diazo bileşiğinin kendi içinde halkalaştığı tespit edilmiştir.

Metal carbenoids are readily generated by metal-catalyzed decomposition of diazoacetates and occupy an established position as versatile synthetic intermediates in organic chemistry. In comparison to free carbenes, metal carbenoids are endowed with increased stability, and are capable of highly selective reactions. They are highly electrophilic but their reactivity profile is very dependent on the structure of the carbenoid and the metal. Most of the early literature on metal-catalyzed carbenoid reactions used copper complexes as the catalysts and ethyl diazoacetate as the carbenoid source. In recent years dirhodium tetracarboxylates have become the catalysts of choice and a much wider range of carbenoid precursors has been developed. Anaç and co-workers have investigated reactions of α, β-unsaturated carbonyl compounds and diazo carbonyl compounds in catalytic medium. In these reactions, dihydrofuran derivatives have been obtained. This product formation is occurred by [1,5]-electrocyclic ring closing reactions. For these reactions are to occur, it is reported that the α, β-unsaturated carbonyl compounds must have hydrogen atom at their β-position with suitable geometry and also, they should favor s-cis conformation. In their continuing report, Anaç’s group determined that sytryldicarbonyls having at least one keto function yielded also dihydrobenzoxepine derivatives by a 1,7-electrocyclization reaction in larger/equal amounts with respect to dihydrofuran derivatives by a 1,5-electrocylization. In this study, benzylidene acetylacetone was treated with dimethyl diazomalonate in the presence of Cu(acac)2 to yield the dihydrofuran and dihydrobenzoxepine in a 1:1.5 ratio. Z- and E-ethyl acetobenzylidene acetates were also reacted under the same conditions to compare the reactivities of conjugated ketone- and ester-ylides in order to obtain formal 1,7-/1,5- electrocyclization reactions in the same studies. In both attempts, the dihydrofuran from ester-ylide and dihydrobenzoxepine from keto-ylide were obtained approximately in the same ratios. They reported that the initially formed keto-/ester-ylides are highly polarized and do not need to undergo 1,5-/1,7-electrocyclization reactions directly, but may rather undergo a rotation around their C( α)-C( β) bonds in order to yield their regiospecific ring closures. According to this study, the ester-ylides did not prefer the formation of dihydrobenzoxepines, whereas the keto-ylides. The reaction of furans with acceptor substituted carbenoids usually leads to unravelling of the heterocycle, resulting in differentially functionalized dienes in good yield. Werker and co-workers determined that Rh2(OAc)4-catalyzed reaction between ethyl diazoacetate with furan revealed the formation of four products including cyclopropane, two isomeric dienes as well as alkylation product. Additionally, cyclopropane is unstable and rearranges to diene upon prolonged standing. The formation of dienes can be proposed from several intermediates. One possibility is that a zwitterionic intermediate forms by electrophilic addition of the carbenoid to the furan ring at the 2-position. In another report, Pirrung’s group demonstrated that furan reacts with 2-diazo-1,3-cyclohexanedione (acceptor–acceptor carbenoid) to generate tricycle in good yield. For this structure would need to be derived from a zwitterionic intermediate derived from attack of the carbenoid at the 3-position, which is electronically unfavored. Pirrung suggested that the regiochemistry is due to the stereoelectronics involved in ringopening of the furanocyclopropane. This reaction has been extended to a range of furan derivatives with variable success. Another report is about reaction of furans with donor–acceptor carbenoids. Davies and co-workers determined that the Rh2(S-DOSP)4-catalyzed reaction of aryldiazoacetates with furan gave predominantly biscyclopropane when aryldiazoacetates was used in a three-fold excess. Most interestingly, when the reaction is conducted with 2,5-dimethylfuran biscyclopropane is formed, which has the opposite sense of absolute configuration to biscyclopropane which mention previous sentence. According to Davies report the donor groups in the donor–acceptor substituted carbenoids seem to make these carbenoids less prone to the formation of zwitterionic intermediates compared to the acceptor carbenoids. However, if electron-donating groups are incorporated into the furan, then zwitterionic transformations can become the dominant reaction pathway. This is clearly seen in the reaction with 2-methoxyfuran with aryldiazoacetate where the dienes become the exclusive products. This is an important consideration, as metal carbenoids that are very electrophilic will tend to react via zwitterionic intermediates while the donor–acceptor carbenoids, and to a lesser extent the acceptor carbenoids, will tend to react in a concerted manner. Very electron-rich heterocycles would also be expected to favor the formation of zwitterionic intermediates. In this thesis, we studied the reactions of three α, β,γ,δ-unsaturated diketone, diester and ketone-ester compounds and four diazo compounds in the presence of copper(II) acethylacetonate [Cu(acac)2] or Rh(II) acetate catalysts. The starting three α, β,γ,δ-unsaturated dicarbonyl compounds, containing the same furan group at their β-positions but having different carbonyl functions were synthesized. These compounds are (E)-dimethyl 2-(3-(furan-2 il)allylidene) malonate, (E)-3-(3-(furan-2-yl)allylidene)pentane-2,4-dione and (2E/Z,4E)-ethyl 2-acetyl-5-(furan-2-yl)penta-2,4-dienoate. Then the reactions of these synthesized three conjugated carbonyls with dimethyl diazomalonate in the presence of copper(II) acetylacetonate/benzene were studied. The reaction of (E)-3-(3-(furan-2-yl)allylidene)pentane-2,4-dione yielded [1,5]-electrocyclic ring closing compound ((E)-dimethyl-acetyl-3-(2-(furan-2-yl)vinyl)-5-methylfuran-2,2(3H)-dicarboxylate) as a sole product. When similar reaction was carried out with (2E/Z,4E)-etyl 2-acetile-5-(furan-2-yl)penta-2,4-dienoate compound, [1,7]-electrocyclic ring closing compound (6-ethyl 2,2-dimethyl 3-(furan-2-yl)-7-methyloxepine-2,2,6(3H)-tricarboxilate) was obtained as a sole product. But in the reaction of (E)-dimethyl 2-(3-(furan-2-yl)allylidene)malonate with dimethyl diazomalonate a ring-opening product of furan function ((3E/Z,6E)-tetramethyl 5-oksonone-1,3,6,8-tetraene-1,1,9,9-tetracarboxilate) was obtained as a sole product. When the reaction was repeated in the presence of Rh(II) acetate, the same product was obtained. In this case, our attention was directed to the the reaction of (E)-dimethyl 2-(3-(furan-2-yl)allylidene)malonate that didn’t yield [1,5]/[1,7]-electrocyclic closure products. So, dimethyl diazomalonate (acceptor-acceptor carbenoid) reactant was altered with ethyl diazoacetate (acceptor), 1-diazo-1-phenylpropane-2-one (donor-acceptor) and (E)-methyl 2-diazo-4-phenylbut-3-enoate) (donor-acceptor). The reaction of (E)-dimethyl 2-(3-(furan-2-yl)allylidene)malonate with ethyl diazoacetate, in the presence of Rh(II) acetate were performed and a ring-opening product ((3E,6E,8E)-9-ethyl 1,1-dimethyl 5-oxonone-1,3,6,8-tetraene-1,1,9-tricarboxilate) was obtained again as a sole product. The same result was endorsed in the presence of copper(II) acetylacetonate catalyst. But in the reactions of the two donor-acceptor diazo compounds (1-diazo-1-phenylpropane-2-one and (E)-methyl 2-diazo-4-phenylbut-3-enoate) poliene derivatives couldn’t be obtained. While the reaction of 1-diazo-1-phenylpropane-2-one in the presence of Rh(II) acetate yielded [1,5]-electrocyclic ring closing compound ((E)-Methyl 5-acetyl-4-(2-(furan-2-yl)vinyl)-2-methoxy-5-phenyl-4,5-dihydrofuran-3-carboxylate, (E)-methyl 2-diazo-4-phenylbut-3-enoate didn’t yield any reaction with other reactant.
Synthesis Of Drug Targeted Carbonyl Compounds
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: δ-Doymamış karbonil bileşikleri; Diazo; Karben; Furan halkası açılma reaksiyonları.; δ-Unsaturated dicarbonyl compounds; Diazo; Carben; Furan ring-opening reactions.